REKONSTRUKSI NILAI KETELADANAN PANEMBAHAN BODHO SEBAGAI INSTRUMEN PENGUATAN KARAKTER IPS - Pungky Mareta Arianti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Social Studies learning has so far been theoretical and less than optimal in instilling character, while the flow of globalization has led to the erosion of noble values among the younger generation. On the other hand, the younger generation is also starting to lose connection with their local historical identity due to the phenomenon of generational amnesia. This study aims to reconstruct the exemplary values of the local figure Panembahan Bodho and formulate their potential as an instrument for character strengthening in Social Studies learning. The research employs a qualitative approach with a library research method. Data collection was conducted through the exploration of various primary and secondary literature sources, including theses, scientific journals, books, and historical documents related to Panembahan Bodho and the Nyadran tradition at Makam Sewu in Bantul, Yogyakarta. The data analysis technique uses content analysis with the Miles and Huberman model. The findings reveal three main results. First, the historical profile of Panembahan Bodho shows a figure as a student of Sunan Kalijaga who chose to dedicate himself to Islamic da'wah, with the nickname